Top‐Down Constraints on Methane Point Source Emissions From Animal Agriculture and Waste Based on New Airborne Measurements in the U.S. Upper Midwest. Issue 1 (7th January 2020) - Yu, Xueying; Millet, Dylan B.; Wells, Kelley C.; Griffis, Timothy J.; Chen, Xin; Baker, John M.; Conley, Stephen A.; Smith, Mackenzie L.; Gvakharia, Alexander; Kort, Eric A.; Plant, Genevieve; Wood, Jeffrey D.
Abstract: Agriculture and waste are thought to account for half or more of the U.S. anthropogenic methane source. However, current bottom‐up inventories contain inherent uncertainties from extrapolating limited in situ measurements to larger scales. Here, we employ new airborne methane measurements over the U.S. Corn Belt and Upper Midwest, among the most intensive agricultural regions in the world, to quantify emissions from an array of key agriculture and waste point sources. Nine of the largest concentrated animal feeding operations in the region and two sugar processing plants were measured, with multiple revisits during summer (August 2017), winter (January 2018), and spring (May–June 2018). We compare the top‐down fluxes with state‐of‐science bottom‐up estimates informed by U.S. Environmental Protection Agency methodology and site‐level animal population and management practices. Top‐down point source emissions are consistent with bottom‐up estimates for beef concentrated animal feeding operations but moderately lower for dairies (by 37% on average) and significantly lower for sugar plants (by 80% on average). Swine facility results are more variable. The assumed bottom‐up seasonality for manure methane emissions is not apparent in the aircraft measurements, which may be due to on‐site management factors that are difficult to capture accurately in national‐scale inventories. If not properly accounted for, such seasonal disparities could lead to source misattribution in top‐down assessments of methane fluxes. Plain Language Summary: Key agricultural methane sources are quantified using new airborne measurements in the U.S. Corn Belt and Upper Midwest. Measurements spanned multiple seasons and targeted nine of the largest concentrated animal feeding operations in the region along with two sugar processing plants. Compared with bottom‐up estimates informed by U.S. Environmental Protection Agency methodology and site‐level animal and management data, top‐down fluxes agree well with bottom‐up estimates for beef but are lower for dairies and sugar plants and suggest a possible mismatch in the timing of emissions. Key Points: We used aircraft measurements to quantify methane emissions from key agricultural point sources in the Upper Midwest during three seasons Top‐down methane fluxes are consistent with bottom‐up values for beef facilities but reveal a mismatch for dairies and sugar plants These discrepancies point to potential spatial and temporal misattribution of emissions used for atmospheric inverse modeling